2019
DOI: 10.1103/physrevd.100.023014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a cosmic-ray origin of the multiwavelength emission in M31

Abstract: A recent detection of spatially extended gamma-ray emission in the central region of the Andromeda galaxy (M31) has led to several possible explanations being put forth, including dark matter annihilation and millisecond pulsars. Another possibility is that the emission in M31 can be accounted for with a purely astrophysical cosmic-ray (CR) scenario. This scenario would lead to a rich multi-wavelength emission that can, in turn, be used to test it. Relativistic cosmic-ray electrons (CRe) in magnetic fields pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 110 publications
1
12
0
Order By: Relevance
“…The other main physical interpretation is that the signal arises from DM, which is thought to be the dominant component in the outer regions of the galaxy. γ-ray emission from M31's inner galaxy has also been detected, but the exact nature of the emission still remains an open question, as the morphology of the signal doesn't appear to trace regions rich in gas and star formation [32,[41][42][43][44][45][46][47]. On the other hand, the total γ-ray luminosity is found to be in general agreement with the wellknown scaling relationship between the γ-ray luminosity and infrared luminosity (8-1000 µm) for star-forming galaxies [48].…”
Section: Introductionmentioning
confidence: 99%
“…The other main physical interpretation is that the signal arises from DM, which is thought to be the dominant component in the outer regions of the galaxy. γ-ray emission from M31's inner galaxy has also been detected, but the exact nature of the emission still remains an open question, as the morphology of the signal doesn't appear to trace regions rich in gas and star formation [32,[41][42][43][44][45][46][47]. On the other hand, the total γ-ray luminosity is found to be in general agreement with the wellknown scaling relationship between the γ-ray luminosity and infrared luminosity (8-1000 µm) for star-forming galaxies [48].…”
Section: Introductionmentioning
confidence: 99%
“…In this Section we summarize the results of the analysis of Fermi-LAT from the M31 region performed in Karwin et al (2019). We will not discuss here the bright 𝛾-ray emission from the IG, whose origin has been debated in (Ackermann et al 2017;Di Mauro et al 2019;McDaniel et al 2019), nor the tenuous diffuse emission from the OH, whose origin might be unrelated to M31 (Karwin et al 2019), but we will rather focus on the 𝛾-ray emission observed from the SH.…”
Section: Summary Of the Relevant 𝛾-Ray Datamentioning
confidence: 99%
“…Ref. [17] points out that the radio and -ray observations of M31 bulge suggest that it hosts an CR electron power of ∼ 10 39 erg s −1 , while SNRs can only inject ∼ 5×10 37 erg s −1 . Interestingly, our model predicts that MSPs can inject ∼ 8 × 10 38 erg s −1 .…”
Section: Takahiro Sudohmentioning
confidence: 99%